Prospecting the theragnostic potential of the psycho-neuro-endocrinological perturbation of the gut-brain-immune axis for improving cardiovascular diseases outcomes - Rajan, Emilda Judith Ezhil; Alwar, Sai Varsaa; Gulati, Richa; Rajiv, Rohan; Mitra, Tridip; Janardhanan, Rajiv (Frontiers in Molecular Biosciences, 2024)
Biological derivatives and their effective influence on psychological parameters are increasingly being deciphered to better understand body-mind perspectives in health. Recent evidence suggests that the gut-brain immune axis is an attractive theragnostic target due to its innate capacity to excite the immune system by activating monocyte exosomes. These exosomes induce spontaneous alterations in the microRNAs within the brain endothelial cells, resulting in an acute inflammatory response with physiological and psychological sequelae, evidenced by anxiety and depression. Exploring the role of the stress models that influence anxiety and depression may reflect on the effect and role of exosomes, shedding light on various physiological responses that explain the contributing factors of cardiovascular disorders. The pathophysiological effects of gut-microbiome dysbiosis are further accentuated by alterations in the glucose metabolism, leading to type 2 diabetes, which is known to be a risk factor for cardiovascular disorders. Understanding the role of exosomes and their implications for cell-to-cell communication, inflammatory responses, and neuronal stress reactions can easily provide insight into the gut-brain immune axis and downstream cardiovascular sequelae.